Assessment of potential predictive value of peripheral blood inflammatory indexes in 26 cases with soft tissue sarcoma treated by pazopanib: a retrospective study - Mirili, Cem (Cancer Manag Res, 2019)
PURPOSE: The aim of this study was to evaluate the prognostic and predictive value of neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (DNLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in soft tissue sarcoma (STS) cases treated with pazopanib. MATERIALS AND METHODS: The study population included 26 STS cases treated with pazopanib for at least 3 months. NLR, DNLR, LMR, and PLR were evaluated at baseline, and at third month of therapy and also compared with response to pazopanib. Median measurements were taken as cutoff for NLR (4.8), DNLR (3.1), LMR (3.6), and PLR (195). The associations between these cutoff values and survival times (progression-free survival [PFS] and overall survival [OS]) were assessed by Kaplan–Meier curves and Cox proportional models. RESULTS: Patients with low pretreatment NLR and DNLR had longer OS (P=0.022, P=0.018), but low PLR was found to be associated only with longer OS. Additionally, decrease in NLR and DNLR after 3 months of therapy as compared with pretreatment measurements was found to be associated with an advantage for OS (P=0.021, P=0.010, respectively) and PFS (P=0.005, P=0.001, respectively). Response to pazopanib; changes in NLR, DNLR, LMR, and PLR; and >3 metastatic sites were found to be independent risk factors in univariate analysis, but NLR was the only independent risk factor in multivariate analysis. CONCLUSION: Low pretreatment and decrease in NLR and DNLR values, and regression/stable disease after 3 months of pazopanib are predictive factors for longer OS and PFS.